Implementation of The Independent Curriculum In Physical Education Learning In Ciasem II State Primary Schools - Prasetio, Hari; Nurhidayah, Helmy; Hamdany, Mochammad; Rahayu, Ega Trisna (Media Ilmu Keolahragaan Indonesia, 2024)
This research aims to explore how the Merdeka Belajar curriculum is applied in Physical Education, Sports and Health (PJOK) learning at Ciasem 2 elementary schools. This research highlights the problem where the Ministry of Education and Culture has issued regulations regarding the Merdeka Belajar curriculum. The method used is descriptive qualitative with the main data source involving the school principal, PJOK teachers and students. Data collection techniques include observation, interviews, and documentation, with data analysis involving data condensation, data presentation, and drawing conclusions. The data collection instrument also involves testing the validity of the data and testing credibility. The results of the research show that the implementation of the Merdeka Belajar curriculum in PJOK learning has been carried out optimally. However, there are obstacles related to teachers' understanding of the concept of the Merdeka Belajar curriculum and the lack of preparation by teachers in implementing it. The successful implementation of the Merdeka Belajar curriculum in PJOK learning is very dependent on the willingness to change in accordance with government regulations and the ability to see existing potential. However, Merdeka Belajar learning planning is not fully in accordance with theory and does not demonstrate the use of CP (Learning Outcomes), ATP (Learning Objective Flow), and MA (Teaching Modules) in the learning process.